FRI0324 Small vessel vasculitis surrounding a preserved temporal artery: a diagnostic algorithm to assess clinical significance. (15th June 2017) - Frigole, G Espigol; Terenas, M; Prieto-Gonzalez, S; Alba, R; Hernandez-Rodriguez, J; Planas-Rigol, E; Corbera-Bellalta, M; Terrades, N; Cid, MC
Abstract : Background: Systemic vasculitides are complex and heterogeneous diseases with overlapping features that frequently pose a diagnostic challenge to clinicians. The temporal artery biopsy (TAB) is the gold standard for the diagnosis of giant cell arteritis (GCA) but, occasionally, TAB show inflammation of small vessels surrounding a spared temporal artery (SVV) as the only pathologic finding. Ultimate diagnosis and, consequently, optimal treatment remain uncertain in these patient. Objectives: To analyze the final diagnosis of patients with SVV surrounding a spared temporal artery after a pre-established diagnostic algorithm and to identify clinical and laboratory findings with potential usefulness in predicting the ultimate diagnosis. Methods: Patients with TAB showing SVV were subjected to the diagnostic algorithm displayed in figure 1, completed by at least 1 year follow-up. Clinical and laboratory features at the time of diagnosis were recorded. The algorithm led to the following final diagnosis: GCA, other systemic vasculitis and undetermined condition. Chi-squared and ANOVA tests were used for statistical comparison using IBM SPSS Statistics 20. Results: From 1998 to 2007, 380 TAB were performed in our institution. Biopsy disclosing small vessel inflammation surrounding a normal temporal artery (SVV) was described in 47 (12%) patients. In all patients TAB was selected as the first invasive procedure because GCA was initially considered the most likely diagnosis. Accordingly, 24 (51%) fulfilled at least 3 ACR classification criteria for GCA. 7 patients declined to undergo subsequent work-up to complete the diagnostic algorithm, 10 died or were lost to follow –up before completing 1 year. All of them were excluded. The study cohort consisted of 30 patients (19 women and 11 men) aged 77±10.4 years followed for 55.16±55.20 months. In 13 patients the final diagnosis was consistent with GCA based on the absence of SVV in other territories, large-vessel inflammation by imaging or subsequent development of aortic aneurysm; in 12 SVV was subsequently demonstrated in other territories and were diagnosed with other systemic vasculitis (7 AAV, 0 cryo, 3 PAN, 0 vasculitis associated to autoimmune diseases, 2 unclassified small vessel vasculitis), and in 5, diagnosis remained undetermined. No significant differences in clinical or routine laboratory abnormalities were found among patient subgroups stratified according to the final diagnosis. Conclusions: Inflammation of small vessels surrounding a spared temporal artery in a TAB conveys a substantial diagnostic uncertainly. After a detailed diagnostic work-up most of patients can be diagnosed with GCA. However other systemic vasculitis requiring more aggressive treatment may disclose similar histopathologic findings and are also frequent and diagnosis remains uncertain in a substantial proportion of cases. Search for more accurate molecular biomarkers is necessary for a better interpretation of these findings Acknowledgements: "Supported by PI15/00092, Plan Estatal de Investigaciόn Científica y Técnica de Innovaciόn 2013–2016 y cofinanciado por el ISCIII-Subdirecciόn General de Evaluaciόn y el Fondo Europeo de Desarrollo Regional (FEDER)" Disclosure of Interest: None declared